Evaluation of occupational health interventions using a randomized controlled trial: challenges and alternative research designs - Schelvis, Roosmarijn MC; Oude Hengel, Karen M.; Burdorf, Alex; Blatter, Birgitte M.; Strijk, Jorien E.; van der Beek, Allard J. (Scandinavian Journal of Work, Environment & Health, 2015)
Occupational health researchers regularly conduct evaluative intervention research for which a randomized controlled trial (RCT) may not be the most appropriate design (eg, effects of policy measures, organizational interventions on work schedules). This article demonstrates the appropriateness of alternative designs for the evaluation of occupational health interventions, which permit causal inferences, formulated along two study design approaches: experimental (stepped-wedge) and observational (propensity scores, instrumental variables, multiple baseline design, interrupted time series, difference-in-difference, and regression discontinuity). For each design, the unique characteristics are presented including the advantages and disadvantages compared to the RCT, illustrated by empirical examples in occupational health. This overview shows that several appropriate alternatives for the RCT design are feasible and available, which may provide sufficiently strong evidence to guide decisions on implementation of interventions in workplaces. Researchers are encouraged to continue exploring these designs and thus contribute to evidence-based occupational health.
Keywords: difference-in-difference; effectiveness; evaluation; experimental study design; instrumental variable; interrupted time series; multiple baseline design; observational study design; occupational health intervention; propensity score; randomized controlled trial; RCT; regression discontinuity; research design; stepped-wedge design